Parasagittal Interlaminar and Transforaminal Epidural Steroid Injections for Radicular Low Back Pain; Which is More Comfortable? - Gevher Rabia Genç Perdecioğlu; Gökhan Yıldız; Ömer Taylan Akkaya; Ezgi Can; Damla Yürük (Turkish Journal of Anaesthesiology and Reanimation, 2023)

(untitled)
Objective: This study aimed to compare parasagittal interlaminar (PS) and transforaminal (TF) epidural steroid injections for unilateral L5 and S1 radicular lower back pain in terms of patient comfort, efficacy, safety, contrast enhancement, and radiation exposure. Methods: This was a prospective randomized single-blind study. A total of 59 participants were included in this study. The visual analog scale (VAS) and Oswestry Disability Index (ODI) were obtained. A comfort questionnaire was administered to all participants. The total fluoroscopy time and contrast distribution levels were recorded. Results: Pre- and post-treatment VAS scores were similar between the groups. The ODI scores increased in favor of the PS group at week 2 (P < 0.041); however, there was no difference between the two groups at other times. The VAS and ODI scores improved significantly with treatment in both the groups (P < 0.001). Total fluoroscopy time was shorter in the PS group (P < 0.001). PS application was more comfortable (P < 0.001). While no complications were observed in the PS group, three complications occurred in the TF group. Anterior epidural contrast spread to three or more levels was observed in 57% of the participants in the PS group, whereas no spread to more than two levels was observed in the TF group. Conclusion: The PS epidural approach is superior to the TF approach in terms of a low incidence of side effects, less radiation exposure, better patient comfort, higher epidural contrast spread, and single-level needle access.